Privacy-preserving protocol for trust and reputation system in VANET - Li, Pengfei (2016)
By utilizing vehicular ad hoc network (VANET), highway vehicle platooning is a promising framework for future driving because of its improved safety, driving experience and traffic utilization. Since the quality of vehicle platooning depends on platoon head (PH) vehicle significantly, trust and reputation system is applied in VANET for PH vehicle’s performance evaluation, in which reputation score is used to rate PH vehicles. However, the reputation score of a PH vehicle may not be accurate enough if the information security of the trust and reputation system is compromised by malicious third party. In this project, a privacy-preserving protocol is proposed for platoon head vehicle’s evaluation in trust and reputation system of VANET. In order to conquer malicious third party’s threats to information security especially threats to confidentiality, integrity and authentication, some techniques such as data encryption, hashing algorithm and digital signature are applied during the feedback data transmission. Additionally, mathematical approaches for calculating PH vehicle’s reputation score are designed to accurately reflect PH vehicle’s performance and the quality of platooning service. Finally, the proposed protocol is implemented by developing an Android application for clients to provide platooning service feedback and a Java program for server to process the feedback data.